Investigating the Effect of Market Orientation on Environmental Performance with the Mediating Role of Green Supply Chain Management Strategies. Case study: Khales Sazan Rooy Company - AZIMI, Hossein; AMIRI, Vahid (Journal of Environmental Management and Tourism, 2018)
In the present era, marketing based on some environmental and social considerations is raised as one of the most important activity of good and service production companies, and green marketing is one of the marketing areas that in environmental issues, many topics have been allocated to it. The purpose of this study is to develop a structural model for investigating the relationship between market orientation and environmental performance and green supply chain management strategies. The research method is a descriptive of type of survey and target population is employees and managers of Khalessazan Rooy Company in Zanjan. A questionnaire was used to collect data and was distributed among 215 employees and managers of the different levels of the company through random stratified sampling. In this research, the modeling of structural equations and partial least squares (PLS) were used to test the hypotheses and fit the model. The results showed that market orientation was effective on the supply chain management strategies. But its impact on environmental performance was rejected. On the other hand, the indirect effect of market orientation has been confirmed through the intermediate variable of supply chain management strategies. Finally, it was revealed that supply chain management approaches have a positive and significant effect on environmental performance.